What Do People Ask Their Social Networks, and Why? A Survey Study of Status Message Q&A Behavior - Morris, Meredith Ringel; Teevan, Jaime; Panovich, Katrina (Proceedings of CHI 2010, 2010)
People often turn to their friends, families, and colleagues when they have questions. The recent, rapid rise of online social networking tools has made doing this on a large scale easy and efficient. In this paper we explore the phenomenon of using social network status messages to ask questions. We conducted a survey of 624 people, asking them to share the questions they have asked and answered of their online social networks. We present detailed data on the frequency of this type of question asking, the types of questions asked, and respondents‟ motivations for asking their social networks rather than using more traditional search tools like Web search engines. We report on the perceived speed and quality of the answers received, as well as what motivates people to respond to questions seen in their friends‟ status messages. We then discuss the implications of our findings for the design of next-generation search tools.